Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) nhận xét hệ số : 1 + 4 - 29 + 24 = 0
=> x3 + 4x2 - 29x + 24 = x2(x-1) + 5x(x-1) - 24(x-1)
= (x-1)(x2+5x-24) = (x-1)(x-3)(x+8)
b) ...
a) \(x^3+4x^2-29x+24\)=\(\left(x+8\right)\left(x^2-4x+3\right)\)=\(\left(x+8\right)\left(x^2-x-3x+3\right)\)=\(\left(x+8\right)\left(x-1\right)\left(x-3\right)\)
b) \(x^4+6x^3+7x^2-6x+1\)=\(x^4+3x^3-x^2+3x^3+9x^2-3x-x^2-3x+1\)=\(x^2\left(x^2+3x-1\right)+3x\left(x^2+3x-1\right)-\left(x^2+3x-1\right)\)=\(\left(x^2+3x-1\right)\left(x^2+3x-1\right)\)=\(\left(x^2+3x-1\right)^2\)
\(x^3+4x^2-29x+24\)
\(=x^2\left(x+8\right)-4x\left(x+8\right)+3\left(x+8\right)\)
\(=\left(x+8\right)\left(x^2-4x+3\right)\)
\(=\left(x+8\right)\left[x\left(x-1\right)-3\left(x-1\right)\right]\)
\(=\left(x+8\right)\left(x-1\right)\left(x-3\right)\)
= -2 ( x2 + 2x + 1 ) + 32
= -2 ( x +1 )2 + 32
= - 2 [ (x + 1 )2 - 16 ]
= -2 [ (x + 1 ) 2 - 42 ]
= -2 ( x + 1 - 4 ) ( x + 1 + 4)
= -2 ( x - 3 ) ( x +5 )
a, \(x^3+4x^2-29x+24\)
\(=x^3-x^2+5x^2-5x-24x+24\)
\(=x^2\left(x-1\right)+5x\left(x-1\right)-24\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2+5x-24\right)\)
\(=\left(x-1\right)\left[x\left(x-3\right)+8\left(x-3\right)\right]\)
\(=\left(x-1\right)\left(x-3\right)\left(x+8\right)\)
\(x^3+6x^2+11x+6\)
\(=x^3+x^2+5x^2+5x+6x+6\)
\(=x^2\left(x+1\right)+5x\left(x+1\right)+6\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2+5x+6\right)\)
\(=\left(x+1\right)\left[x\left(x+2\right)+3\left(x+2\right)\right]\)
\(=\left(x+1\right)\left(x+2\right)\left(x+3\right)\)
Chúc bạn học tốt.
\(=x^3+1+2x^2+2x\)
\(=\left(x+1\right)\left(x^2-x+1\right)+2x\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-x+1+2x\right)\)
\(=\left(x+1\right)\left(x^2+x+1\right)\)
\(\Leftrightarrow x^3-3x^2-3x^2+9x-10x+30\)
\(\Leftrightarrow x^2\left(x-3\right)-3x\left(x-3\right)-10\left(x-3\right)\)
\(\Leftrightarrow\left(x-3\right)\left(x^2-3x-10\right)\)
\(\Leftrightarrow\left(x-3\right)\left(x-5\right)\left(x+2\right)\)
\(=\left(x^3-2x^2\right)+\left(8x^2-16x\right)+\left(15x-30\right)\)
\(=x^2\left(x-2\right)+8x\left(x-2\right)+15\left(x-2\right)\)
\(=\left(x-2\right)\left(x^2+8x+15\right)\)
\(=\left(x-2\right)\left(x^2+3x+5x+15\right)\)
\(=\left(x-2\right)\left[x\left(x+3\right)+5\left(x+3\right)\right]\)
\(=\left(x-2\right)\left(x+3\right)\left(x+5\right)\)
\(x^3+2x^2-29x-30=\left(x^3+x^2\right)+\left(x^2+x\right)-\left(30x+30\right)\)
\(=x^2\left(x+1\right)+x\left(x+1\right)-30\left(x+1\right)=\left(x+1\right)\left(x^2+x-30\right)\)
\(=\left(x+1\right)\left(x^2+6x-5x-30\right)=\left(x+1\right)\left[x\left(x+6\right)-5\left(x+6\right)\right]=\left(x+1\right)\left(x-5\right)\left(x+6\right)\)